2012
DOI: 10.1007/s11033-012-2060-7
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the genetic effects of prolactin gene polymorphisms on chicken egg production

Abstract: Chicken prolactin (PRL) is a physiological candidate gene for egg production. Variations of T8052C and G8113C in exon 5 of PRL gene may associate with chicken egg production. The objective of the study was to investigate the association of these two single nucleotide polymorphisms in PRL gene with egg production of Recessive White chickens and Qingyuan Partridge chickens. Genotyping was performed by polymerase chain reaction-ligase detection reaction (PCR-LDR) method. The T8052C and G8113C of PRL were signific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
17
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 19 publications
5
17
1
1
Order By: Relevance
“…Because eggs are the main products in the laying hen farm, and the egg production rate determines the breeding e ciency. Therefore, improvement of the egg production has an important economic value [40]. In this study, compared with the control group, the average egg production rate in the antibiotic group, experimental group I, and experimental group II were increased signi cantly (P < 0.01).…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…Because eggs are the main products in the laying hen farm, and the egg production rate determines the breeding e ciency. Therefore, improvement of the egg production has an important economic value [40]. In this study, compared with the control group, the average egg production rate in the antibiotic group, experimental group I, and experimental group II were increased signi cantly (P < 0.01).…”
Section: Discussionmentioning
confidence: 62%
“…Many studies suggested that adding Bacillus sp. to the diet of hens can increase the eggshell thickness and eggshell strength, improve the quality of eggshell, reduce the rate of broken eggs, and improve the economic bene ts of poultry farms [40,44]. Similarly, it was also reported that the addition of B. subtilus to the diet improved the haugh unit and protein index signi cantly, and the thickness of eggshell was also improved [41].…”
Section: Egg Qualitymentioning
confidence: 91%
“…The latter in layers is particularly important for reproductive aspects, which involve different hormones and their receptors e.g. growth hormone (GH), prolactin (PRL), thyroids, luteinizing hormone (LH), melatonin, and others [ 35 , 36 ]. For instance, GH is a regulator of ovarian and oviductal functions in chicken, acting in the modulation of LH and the synthesis of insulin-like growth factors [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…For instance, GH is a regulator of ovarian and oviductal functions in chicken, acting in the modulation of LH and the synthesis of insulin-like growth factors [ 35 ]. Also, prolactin is involved with different physiological processes that are important for poultry reproduction; hence, PRL is a candidate gene for egg production in chicken [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Ces caractères étant directement en lien avec les fonctions de reproduction, la majorité des études ont été, comme précédemment, des approches « gène-candidat » ciblantdes gènes connus dans la régulation de la reproduction. Ainsi, les gènes codant pour la prolactine (PRL) (Chromosome 2), le récepteur à la GnRH (Chromosome 22) ou encore le récepteur à la FSH (Chromosome 3) ont été identifiés comme influençant le caractère EN(Bhattacharya et al 2011a, Fatemi et al 2012, Liu et al 2012, Li et al 2013. La GnRH, la FSH et la PRL sont impliquées dans la folliculogénèse.Des QTL communs aux deux caractères ont également été identifiés.…”
unclassified